Tales from a not-so-talented pop star - Russell, Rachel Renée (Russell, Rachel Renée. Dork diaries, 2011)
When scholarship student Nikki Maxwell, whose father is the school exterminator, decides to enter the talent show at her expensive private school, her nemesis MacKenzie threatens to reveal Nikki's status to the rest of the school.